Jalan Terjal Redistribusi Tanah Menuju Pemerataan Kepemilikan Hak Atas Tanah di Kabupaten Pasaman - Saimar, Hamda Afsuri; Fendri, Azmi; Fatimah, Titin (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2024)
Failure to implement good land redistribution to the community will lead to gaps in ownership of land rights in Indonesia. Implementation of land redistribution in accordance with expectations can at least ensure equal distribution of ownership of land rights, realize the optimization of agricultural land, and increase income for the people of Pasaman Regency. This research aims to examine the implementation of land redistribution, especially for the period 2021–2022, in Pasaman Regency in response to the challenge of equitable ownership of land rights. This research uses an empirical juridical approach; the nature of the research is descriptive and analytical; data collection techniques are carried out using interviews and document studies. The final results show that the implementation of land redistribution in Pasaman Regency, if seen in the last two years, is still considered to be less effective in realizing equal distribution of ownership of land rights. The lack of precise targets and the failure to achieve these targets impact the effectiveness of land redistribution. With the various challenges and prospects that are expected in the future, it is necessary to adapt policies to several agrarian reform events, such as the concept of land reform in Ngandagan Village and the proposed requirements for establishing cooperatives that were implemented in Nagari Timpe. Tidak terlaksananya redistribusi tanah yang baik kepada masyarakat akan menyebabkan terjadinya kesenjangan kepemilikan hak atas tanah di Indonesia. Pelaksanaan redistribusi tanah yang sesuai dengan harapan setidaknya dapat memastikan pemerataan kepemilikan hak atas tanah, terwujudnya optimalisasi lahan pertanian dan meningkatkan pendapatan bagi masyarakat Kabupaten Pasaman. Penelitian ini bertujuan untuk mengkaji pelaksanaan redistribusi tanah, terutama periode tahun 2021 dan tahun 2022 di Kabupaten Pasaman dalam menjawab tantangan pemerataan kepemilikan hak atas tanah. Penelitian ini menggunakan pendekatan yuridis empiris, sifat penelitian deskriptif analitis, teknik pengumpulan data dilakukan dengan wawancara dan studi dokumen. Hasil akhir menunjukkan bahwa pelaksanaan redistribusi tanah di Kabupaten Pasaman jika dilihat dalam dua tahun terakhir masih dinilai kurang efektif dalam mewujudkan pemerataan kepemilikan hak atas tanah. Hal ini dipengaruhi oleh kurang tepatnya sasaran dan tidak tercapainya target pelaksanaan redistribusi tanah. Dengan berbagai tantangan beserta prospek yang diharapkan kedepannya diperlukan adaptasi kebijakan terhadap beberapa peristiwa pembaruan agraria seperti konsep landreform di Desa Ngandagan dan pengajuan persyaratan pendirian koperasi yang dilaksanakan di Nagari Timpe.